Risk-taking influences perceived dominance, prestige, and leadership endorsement in Japanese adults - Ono, Akira; Meng, Xianwei (Frontiers in Psychology, 2025)
Risk-taking behavior occurs everywhere in our social lives, but little is known about how it is socially evaluated. Previous research has shown that risk-taking functions as a signal of a risk-taker’s dominance and prestige, increasing their likelihood of being endorsed as a leader in intergroup competitive contexts. However, the findings were obtained from Western cultures, leaving it unclear how these social evaluations are made in other cultures. This study investigated the social evaluations of risk-takers among Japanese individuals, who are rooted in Eastern culture which has been known that many social norms and traditions differ from Western cultures. Through a survey-based investigation (N = 299), we found that while risk-takers are perceived as more dominant, there was no difference in prestige evaluation between risk-takers and risk-avoiders. Moreover, leadership endorsement varies across contexts, with risk-taking increasing endorsement in competitive situations but decreasing it in cooperative ones, mediated by perceived dominance. These findings not only clarified the social evaluation of risk-taking behavior in one of the Eastern cultures but also provided insights into nuanced perceptions of risk-takers across diverse cultural settings.